Progress on visual display terminal syndrome in children - Xiao-Fang Ren (Guoji Yanke Zazhi, 2013)
With the rapid development of information era, video display terminal(VDT)has entered people's lives, and the operator's health problems have been recognized, which is so called VDT syndrome. At the same time, the frequency of children's exposure to the VDT is higher and higher. Childhood is the critical period of visual development. As the data show that the excessive use of VDT can cause eye fatigue, myopia, dry eye, abnormal blinking, headache and other symptoms. In this article, we will talk about the symptoms, mechanism, and the prevention and treatment of children's VDT syndrome.